Levels and Health Risk Assessments of Cd and Pb in Pomadasys maculatus Marketed by Karachi Fish Harbor, Pakistan - Quratulan Ahmed; Levent Bat (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Aim of this study was to measure cadmium and lead concentrations in the edible tissues of Saddle grunt Pomadasys maculatus (Bloch, 1793) from Karachi Fish Harbor different seasons of the year 2011.  Results showed that the concentration varied from 0.18 to 1.14 with a mean of 0.59 ± 0.05 mg.kg-1 for Cd and from 0.02 to 1.54 with a mean of 0.54 ± 0.05 mg.kg-1 for Pb. These concentrations are higher than the maximum permissible values in European and other international regulations (Global Agricultural Information Network Report for China, Russian Federation , Australia New Zealand Food Standards, Georgian Food Safety Rules, Turkish Food Codex and the Ministry of Agriculture, Fisheries and Food). However the average weekly intakes of Cd and Pb per body weight values (minimum-maximum) were 0.021 (0.0063-0.0399) and 0.019 (0.0007-0.0539)mg.week-1.70 kg body weight-1, respectively and not exceeded the Provisional Tolerable Weekly Intake (PTWI) established. Consumption of Saddle grunt from the Karachi coasts of Pakistan can therefore be said to constitute no health risks so far as the heavy metals investigated are concerned. However, due to the Cd and Pb muscle levels exceeded the maximum levels of fish permitted for human consumption, a plausible health risk could be posed by long-term exposed through Saddle grunt consumption. Keywords: Lead, Cadmium, Pomadasys maculatus, Karachi coast, Pakistan